Development of Student Creativity in Social Studies Learning Based on Infographic Project - Nuansa Bayu Segara,; Evy Nazilatun Nikmah,; Niswatin,; Ali Imron,; Hendri Prastiyono, (Technium Social Sciences Journal, 2023)
Creativity is one of the competencies in 21st-century skills. It needs to be developed in schools through creative social studies learning processes. Project-based learning can be an option to train students to think creatively. This article aims to describe the development of student creativity by applying infographic project-based learning. The research approach is qualitatively descriptive. The subjects of the study were 32 students in the seventh grade at SMP Negeri 42 Surabaya. Data collection techniques include activity observation, non-structuring interviews, and documentation product assessments. The research instruments used creativity rubrics and infographic product rubrics. Data validation is carried out using triangulation techniques. Namely, confirmation is carried out through the results of observation sheets, interviews, and product assessments. End of data analysis using interactive techniques. The results showed that project-based learning can increase the development of student creativity. Improvement occurs at every stage of project-based learning in every aspect and indicator of creativity.